2019
DOI: 10.1177/1055665619874613
|View full text |Cite
|
Sign up to set email alerts
|

A Cone-Beam Computed Tomographic Study of Alveolar Bone Morphology in Patients With Unilateral Cleft Lip and Palate

Abstract: Objective: To evaluate the bony support around the teeth adjacent to the unilateral cleft lip and palate (ULCLP) using cone-beam computed tomography. Methods and Materials: Cone-beam computed tomographies of 48 cleft-adjacent teeth (28 anterior and 20 posterior to the cleft) and 48 noncleft control teeth were evaluated. The alveolar bone thickness at 3 and 6 mm apical to the cement–enamel junction (CEJ), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…23 Teeth adjacent to cleft sites have less alveolar bony support. 28,31,32 Woods et al observed that the cleft facing surface of the root had 5.7% less bony coverage compared to the contralateral tooth. 28 Ercan et al also reported that the tooth adjacent to the cleft had reduced bony support on the buccal surface.…”
Section: Discussionmentioning
confidence: 99%
“…23 Teeth adjacent to cleft sites have less alveolar bony support. 28,31,32 Woods et al observed that the cleft facing surface of the root had 5.7% less bony coverage compared to the contralateral tooth. 28 Ercan et al also reported that the tooth adjacent to the cleft had reduced bony support on the buccal surface.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT is able to portray thickness and height of the alveolar bone, particularly on the buccal and palatal sides. Conventional, 2D dental radiography cannot provide such information [ 16 ]. Furthermore, the previous studies have demonstrated how pre-surgical knowledge of the exact volume of bone graft needed can improve surgical results [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alveolar bone on the buccal and palatal sides of teeth anterior to the cleft is significantly thinner compared to teeth unaffected by a cleft [ 14 ]. The lack of alveolar bone results in poor periodontal support for teeth adjacent to the cleft margins, increasing the risk of early tooth loss.…”
Section: Introductionmentioning
confidence: 99%